Legal Liability of Digital Platforms for Default in Electronic Agreements - Sinulingga, Tommy Aditia; Magda, Marienna; Aisyah, Aisyah; Susanto, Ayub Umboyo (Leges Privatae, 2026)
The development of information technology has driven a fundamental shift in the practice of civil agreements through the use of electronic agreements mediated by digital platforms. These changes not only affect the form of the agreement, but also the structure of legal relations, the bargaining position of the parties, and the pattern of accountability for achievement violations. The phenomenon of default in electronic agreements shows a higher complexity than conventional agreements due to the involvement of technological systems and the dominance of digital platforms in controlling the transaction process. This study aims to analyze the juridical construction of electronic agreements and defaults, examine the legal position and scope of responsibility of digital platforms, and examine the implementation of these liability arrangements in positive Indonesian law. The research method used is normative juridical with a legislative, conceptual, and analytical approach, through the review of Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 1 of 2024, Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, and Government Regulation Number 80 of 2019 concerning Trade Through Electronic Systems. The results of the study show that digital platforms cannot be positioned as neutral intermediaries because they have significant control over the transaction ecosystem. Existing arrangements have not established an integrated liability regime, thus opening up space for legal uncertainty and inequality of protection for users. This research emphasizes the urgency of the normative reconstruction of the legal responsibility of digital platforms oriented towards contractual fairness and proportionate risk distribution